Technology and youth growing up in a digital world - Blair, Sampson Lee.; Claster, Patricia Neff.; Claster, Samuel M. (Bingley, U.K. : Emerald, 2015)
This volume focuses on the theme of technology and youth; advancements in communication and leisure technologies over the past decade have radically transformed the role of technology in the lives of youth. Around the globe, children and adolescents are often seen as being the first to embrace new technologies, such as new forms of social media. Having a cell phone, once regarded as an adult technology, has become a necessity within youth culture in many societies. Even video games, once limited to stand-alone computers, have become a venue for social gatherings of youth. The rapid pace of technological advancement has brought about profound changes in the very nature of childhood and adolescence. This volume of examines the role of technology in the lives of children and adolescents. Topics addressed include: cyberbullying, video games and aggressive behavior, online gaming and the development of social skills, sexuality, child pornography, virtual communities for children, social networking and peer relations, and other related issues.
Cyberbullying in the era of digital relationships : the unique role of resilience and emotion regulation on adolescents' adjustment / Giovanna Gianesini, Antonella Brighi -- Factors that influence bystander behavior in the cyberbully context / Jessica Niblack, Jodie L. Hertzog -- Cell phone use and youth perceptions of communication in South Africa / Radhamany Sooryamoorthy -- Adolescents' self-defining internet experiences / A<U+030a>sa Andersson ... [et al.] -- Young collegians : between the physical and numerical territories, different processes of individuation / Elmir de Almeida ... [et al.] -- Keep calm : youth navigating adult authority across networked publics / Ana Campos-Holland ... [et al.] -- All the web's a stage : the effects of design and modality on youth performances of identity / Harry T. Dyer -- n00bs, trolls, and idols : boundary-making among digital youth / Matthew H. Rafalow -- The impact of information and communication technology (ICT) usage on psychological well-being among urban youth / LaToya O'Neal Coleman ... [et al.] -- A longitudinal examination of the relationship between technology use and substance use during adolescence / Christine McCauley Ohannessian -- Sexting, digital dissent and narratives of innocence : controlling the child's body / Brian Simpson -- Technology and the fostered child : a new social work response / Jennifer E. Simpson -- "That is so not true" : adolescent perspectives of adult misconceptions of teen text messaging / Sarah Tulane, J. Mitchell Vaterlaus, Troy E. Beckert -- Watching television and reading achievement : a study of third grade language minority students / Gregory J. Mills -- Can media consumption predict immigrant adolescents' acculturation-related risky health behavior? An analysis of Latino sample in CHIS survey / Yuping Mao, Lu Shi -- United future leaders : a case of the use of technology in youth programming and hidden curriculum / Erin Kostina-Ritchey ... [et al.].
Print version record
Keywords: Social Science -- Children's Studies; Family & Relationships -- Life Stages -- Adolescence; Family & Relationships -- Life Stages -- School Age; Age groups: children; Age groups: adolescents; Sociology: family & relationships; Technology and children; Internet and children; Digital media; Mass media and children; Digital electronics